Shans - new red clover variety - O. L. Onuchina; M. N. Gripas’; E. G. Arzamasova; E. V. Popova; I. A. Korneva (Аграрная наука Евро-Северо-Востока, 2017)
The article presents results of breeding activity (1990.2012) on creation of early, winter hardiness, productive red clover (Trifolium pratense L.) variety ‘Shans’ having high fodder quality. Originators of the variety - Falenki breeding station and North-East Agricultural Research Institute Variety ‘Shans’ (breeding line 804/90) created by a method of multiple biotypic selection from middle-ripening adaptive variety ‘Dymkovsky’. According to the results of competitive tests in Falenki breeding station (2008.2012), the variety had advantage over standard variety ‘Trio’ by main economic traits and distinguished with earliness (55.75 days from spring re-growth till beginning of flowering; 110.128 days for seed ripening), high winter hardiness (96.100 %), dry matter yield - 11.3 t/ha and raw protein yield - 1.53 t/ha, high seed yield - 0.2 t/ha, resistance against root rot (index of disease development IDD = 18.2 %). According to data of ecological test (2012) under agro-climatic conditions of Kirov city (North-East Agricultural Institute) variety ‘Shans’ shown high potential productivity of dry matter - 21.22 t/ha (significantly higher than standard ‘Trio’ on 2.80 t/ha or 15.2%). In 2012 the variety was passed to State varietal test, since 2017 - was included into State Register of breeding achievements allowed to use in Volga-Vyatka region (patent № 8916 from February 13, 2017).